Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.5216/cab.v14i3.15414
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento De Fungos Toxigênicos E Aflatoxinas Em Rações Utilizadas Em Piscicultura

Abstract: The aim of this study was to determine the occurrence of fungi and aflatoxins in fish feeds. We analyzed 36 samples of feed for fish, with two protein compositions (juvenile/fattening) and two forms of use (sealed/open). Aspergillus and Penicillium species were counted, isolated and identified, the toxic capacity of Flavi strains was measured and aflatoxins in the feed were researched. The mean fungal counts ranged from 2.96 to 4.00 log10 CFU/g and there was no significant difference between treatments. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
2
9
0
5
Order By: Relevance
“…Moderate levels of fungal counts were determined on DRBC (<10 to 4.2 × 10 4 UFC/g) and DG18 (xerophilic fungi) (<10 to 3.6 × 10 4 UFC/g). Similar results were reported in Brazil on finished fish feeds [ 40 , 45 ]. However, Nunes [ 49 ] reported values lower than 1 × 10 7 UFC/g on ration formulated for fish feed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moderate levels of fungal counts were determined on DRBC (<10 to 4.2 × 10 4 UFC/g) and DG18 (xerophilic fungi) (<10 to 3.6 × 10 4 UFC/g). Similar results were reported in Brazil on finished fish feeds [ 40 , 45 ]. However, Nunes [ 49 ] reported values lower than 1 × 10 7 UFC/g on ration formulated for fish feed.…”
Section: Discussionsupporting
confidence: 89%
“…There are previous works reporting the presence of one or two toxins, in particular in commercial fish feed or fish organs [ 8 , 12 , 19 , 21 , 38 , 39 , 40 ]. However, recent studies and literature reviews have shown that different kinds of finished animal feeds were co-contaminated with several different toxins, which is the more likely situation [ 9 , 10 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…A ração animal é uma porção de alimento que é fornecida aos animais, composta de diversos ingredientes e formulada de acordo com as necessidades nutricionais de cada indivíduo, considerando fatores como a idade e a espécie. A ração representa um dos principais custos operacionais na produção animal (CARDOSO FILHO et al, 2013), sendo que aproximadamente 60% dos custos operacionais na aquicultura são devido à alimentação de peixes (FAO, 2014).…”
Section: Contaminação Da Ração Utilizada Em Pisciculturaunclassified
“…No Egito,Abdelhamid et al (1998) detectaram altos níveis de aflatoxinas (> 1000 ppb) em ração comercial utilizada para a produção de peixe. Os efeitos adversos em peixes de viveiro atribuídos a essas contaminações por micotoxinas naturais não são suficientemente bem elucidados.A contaminação das rações por micotoxinas pode reduzir o desempenho e afetar o estado geral de saúde do animal, causando diminuição da produtividade, problemas reprodutivos, vulnerabilidade a infecções, aumento da morbidade e até mortalidade(MANDARINO, 1989;CARDOSO FILHO, 2013). O primeiro caso registrado de mortalidade em peixes causado por micotoxinas ocorreu no começo da década de 60, na Califórnia, em que peixes da espécie truta arco-íris consumiram ração com farelo de algodão contaminado por aflatoxinas(HALVER, 2001) Lopes et al (2005).…”
unclassified
See 1 more Smart Citation